Hagiografija v luči sodobnih raziskav - Bošnjak, Blanka (2023)
Hagiography in the Light of Contemporary Research. The scientific monograph Hagiography in the Light of Contemporary Research is comprised of twenty chapters divided into four sections, which cover the phenomenologically diverse hagiographic production in a systematic theoretical manner or through case studies: the first set of chapters deals with the literary-historical, narratological, linguistic and dialectological perspectives on hagiographic discourse from the second half of the 18th century to the beginning of the 20th century, and the second set of chapters deals with hagiographic discourse from the second half of the 18th century to the beginning of the 20th century, and the first set of chapters deals with hagiographic discourse from the second half of the 18th century to the beginning of the 20th century. The second set of chapters raises questions of interdisciplinary, transdisciplinary and cultural studies concepts of hagiography; the third set of chapters develops an understanding of hagiographic discourse in relation to biographical, historiographical, adjectival, legendary and paremiological discourse; and the fourth set of chapters in the monograph presents the process of the canonization of saints and saintesses, and cultural saints and saintesses over time. The aim of the monograph is to emphasize the diversity of species-genre, genre, narratological perspectives of hagiographic discourse, to highlight different methodological and conceptual starting points, where an important role is played by the inclusion of the interweaving of cultural studies concepts in the study of hagiographies and hagiographic processes, the definition of their place ¬in the European context, including the Latin and Byzantine medieval hagiographic creativity, and the highlighting of the important role of foreign-language templates.
Keywords: hagiography; hagiographic discourse; saints; saintesses; canonization process; cultural saints and saintesses